Diverse Eurasian Winter Temperature Responses to Barents‐Kara Sea Ice Anomalies of Different Magnitudes and Seasonality. Issue 13 (6th July 2021) - Zhang, Ruonan; Screen, James A.
Abstract: The sea‐ice‐driven component of observed Eurasian temperature variability, estimated by comparing multimodel large‐ensemble simulations prescribed with either time‐varying or climatological sea‐ice, suggests an intermittent causal effect of Barents‐Kara sea‐ice on Eurasian winter temperature. To understand this intermittency better, bespoke atmospheric model experiments were conducted with the seasonality, sign, and magnitude of sea‐ice anomalies systematically altered. Stronger Eurasian cooling is found in response to modest than to large autumn sea‐ice loss because of nonlinear wave‐mean‐flow interactions that, via a stratospheric pathway, govern the dynamical responses. Winter sea‐ice loss tends to induce Eurasian warming, via thermodynamical effects, which scale approximately linearly with the magnitude of sea‐ice loss. Complete loss of sea‐ice led to Eurasian warming, suggesting the thermodynamical response dominates when sea‐ice loss is sufficiently large. Our results have implications for the stationarity, or lack thereof, of Arctic‐to‐midlatitude connections, and also for reconciling discrepancies between model experiments with different sea‐ice perturbations. Plain Language Summary: Declining sea‐ice is having profound impacts in the Arctic. Scientists are eager to work out if and how Arctic sea‐ice affects weather and climate in mid‐latitudes. Years with below‐average sea‐ice in the Barents‐Kara seas, which lie north of Norway and western Russia, tend to coincide with colder winters over Eurasia, and vice versa. However, not all years with reduced sea‐ice are accompanied by colder winters. Is possible that winter temperatures in Eurasia depend on the magnitude of sea‐ice anomalies and their seasonality, in which seasons they occur, that are different from year to year. To test this idea, we performed bespoke atmospheric model experiments with the sign, magnitude, and seasonality of sea‐ice anomalies systematically altered. Diverse Eurasian winter temperature responses were seen across these experiments. Eurasian cooling was found mostly in experiments with below‐average autumn sea‐ice, whereas warming was mostly found in experiments with above‐average winter sea‐ice. Colder winters were found when sea‐ice loss was modest than it was large. Modest ice loss caused local warming in the Arctic and accompanying changes in the atmospheric circulation led to cooling over Eurasia. When sea‐ice loss was sufficiently large, the associated warming dominated, reaching as far south as Eurasia. Key Points: Multimodel large‐ensemble simulations suggest an intermittent relationship between Barents‐Kara sea‐ice and Eurasian winter temperature Dynamically driven Eurasian winter cooling response to autumn sea‐ice loss is nonlinear, with maximum, cooling from modest ice anomalies Thermodynamically driven Eurasian winter warming in response to winter sea‐ice loss scales linearly with the magnitude of ice anomalies